Pendidikan Musik dalam Bingkai Pengalaman Estetis dan Kultural - Riyan Hidayatullah (Program Studi Pendidikan Musik FBS UNP, 2022)
Music education can be seen from two dimensions. First, as a contagion concept whose output is musical skills inherent in a person. Second, music education is a means to achieve certain learning goals. For example, music is used to teach children about the environment. At this level, music education is used as a tool to introduce someone to musical experiences. Musical experience can be done with an emphasis on aesthetic and cultural values. This notion is done by providing insight that develops learning to apply the values of creation and appreciation. This conceptual article attempts to generate ideas and justifications for the concepts of music education in order to make an original contribution in the form of key and logical arguments that are communicated effectively. Learning experiences that are supported by these aspects make a person educated musically. Aesthetics relates to the values of goodness and beauty that can be transmitted. Meanwhile, culture is a means of introducing and strengthening identity. These strategies are concepts embodied in music education.